Pembinaan Religiusitas Peserta Didik Melalui Kegiatan Amaliyah Jumat Di SD Plus Murung Pudak - Aunia Ulfah; Muhammad Husni; Ubaidillah Ubaidillah (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2026)
This study aims to describe the implementation of Amaliyah Jumat activities as an effort to develop the religiosity of students at SD Plus Murung Pudak. This research employs a qualitative approach with a case study design. Data sources consist of the school principal, Islamic Religious Education (PAI) teachers, activity supervisors, and students of grades IV–VI. Data were collected through participatory observation, in-depth interviews, and documentation. Data validity was verified using source triangulation and technique triangulation. Data analysis followed the Miles, Huberman, and Saldana interactive model, encompassing data condensation, data display, and conclusion drawing. This study specifically focuses on Muslim students who participate in the Amaliyah Jumat program, while non-Muslim students conduct their own worship activities in a school-designated hall and also take part in almsgiving as a shared expression of social solidarity. The findings indicate that: (1) Amaliyah Jumat activities at SD Plus Murung Pudak are held every Friday, covering congregational Dhuha prayer, Quranic recitation, short religious speeches delivered by students, and almsgiving participated in by students of all faiths; (2) these activities consistently contribute to the enhancement of five dimensions of student religiosity, namely the ideological, ritualistic, experiential, intellectual, and consequential dimensions; (3) the primary supporting factors are the commitment of school leadership, teacher exemplary conduct, and parental support, while the inhibiting factors include time constraints and inconsistency among some students. These findings confirm that a structured and sustained Amaliyah Jumat program constitutes an effective instrument for fostering student religiosity in elementary schools, in alignment with the vision of SD Plus Murung Pudak, which upholds faith and piety as the foundation of education.